Extrinsic Activation of Human Coagulation Factors IX and X on the Endothelial Surface - Bom, Victor J J; van Hinsbergh, Victor W M; Reinalda-Poot, Hanneke H; Mohanlal, Ramon W; Bertina, Rogier M (Thrombosis and Haemostasis, 1991)
In previous kinetic studies, the catalytic efficiency of the activation of human coagulation factors IX and X by factor VIIa in the presence of purified tissue factor apoprotein was found to be essentially equal. These activation reactions were now studied on the surface of human umbilical vein endothelial cells. The cells were stimulated with endotoxin to express tissue factor. This tissue factor activity was saturable with factor VIIa and could be inhibited by rabbit antibodies against human tissue factor apoprotein. Only stimulated cells supported factor VIIa activity. No difference in the reactivity of factor VII and VIIa was observed in the presence of factor X, due to rapid feedback activation of factor VII by factor Xa. However, the activation of factor IX by factor VII shows a 10 min lag-phase, which reflects that the activation of factor VII by factor IXa is a less efficient process. The kinetic parameters for the factor VIIa dependent activation of factor IX and factor X on the endothelial surface were: Km 0.09 εM, Vmax 0.13 pmol/min, and Km 0.071 εM, Vmax 0.41 pmol/min, respectively. The same ratio between the Vmax for factor X and factor IX activation was observed as in a cell free system. However, the Km of factor IX was 4-fold higher on the endothelial surface than in the cell free system. Together, these kinetic parameters will favour factor X activation 5-fold over factor IX activation at physiological concentrations of these proteins.The activation of factor X by factor VIIa on the endothelial surface was characterized by a short lag-phase, which was absent in factor IX activation. Further, both the activation of factor X and factor IX were down regulated by factor Xa.